International Open Access Week: Opening Oxford's climate research - Humphreys, S; Partridge, J; Springmann, M; Mhishi, L; Grecksch, K; Budnitz, H; Omukuti, J (Bodleian Libraries, University of Oxford, 2022)
In line with this year’s #OAWeek theme: Open for Climate Justice; this online event, Opening Oxford’s Climate Research aimed to showcase climate research and open practice at Oxford.